Genetic parameters and correlation studies in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Present study carried out with total 154 genotypes including 150 test genotypes and four checks (RH-1566, RH-1499-30, RH-749 and RH-8812) of Indian mustard. These genotypes were evaluated for seed yield and its yield components for eleven characters during rabi season of 2020-21 at CCS Haryana Agricultural University, Hisar. Analysis of variance showed highly significant genotypic difference for all the studied traits. The maximum variability (21.2%) was recorded for test weight and minimum for oil content (0.8%). The two characters namely, secondary branches/plant (91.7%) and test weight (89.6%) had very high broad sense heritability while, genetic advance was relatively high for test weight (41.4%), number of secondary branches/plant (37.2%) and seed yield/plant (31.6%). The results revealed that plant height, number of primary branches/plant, number of secondary branches/plant, main shoot length, number of siliqua on main shoot, siliquae length, number of seeds per siliqua and test weight have significant positive association with seed yield/plant, while path analysis revealed that number of primary branches/plant, number of secondary branches/ plant and siliqua length had the highest positive direct effects on seed yield/plant. All the traits have showed high heritability. The characters identified above as indirect yield components in formulating effective selection strategy for developing high yielding mustard genotypes.